ANALISIS PENGARUH PELAPORAN KEBERLANJUTAN TERHADAP KINERJA DAN NILAI PERUSAHAAN - Tri Ayu Astari; Nuraini Sari (Jurnal Akuntansi dan Keuangan (JAK), 2023)
This research was conducted to determine the effect of disclosing economic, environmental, and social performance in Sustainability Reporting by state-owned companies on company performance and value. This research was conducted on state-owned companies registered in the IDX BUMN20 for the 2016–2020 period and used purposive sampling technique as the sampling method and panel data regression as the analysis method. The result was disclosure of environmental performance had a significant effect on the performance of 17 state-owned companies. However, disclosure of economic, environmental and social performance simultaneously has a significant effect on the performance and value of 17 state-owned companies.